2017
DOI: 10.9734/arjom/2017/36377
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric Stepwise Procedure for Identification of Maximum Safe Dose (MSD)

Abstract: In this article we consider identification of maximum safe dose (MSD) in a dose response study for distribution-free endpoints. Where the maximum safe dose is the highest dose level that does not exceed the median toxicity of the zero dose by a predetermined margin. A nonparametric confidence set-based approach was proposed, that is we incorporate Mann-Whitney method with the partitioning principle in a step-down fashion for safety evaluation. A comprehensive study of the familywise error rate for our new proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, once stepwise confidence intervals are derived, it becomes easy to show that directional errors (that is, correct side decisions at each step) are simultaneously controlled with the familywise error rate (FWER). Adjabui, Howard and Luguterah (2017) proposed a simultaneous nonparametric upper bound procedure based on the Wilcoxon Mann-Whitney test in situations when normal assumptions are violated. Their paper incorporated the partitioning principle for confidence sets procedure proposed by Hsu and Berger (1999) for estimating MSD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, once stepwise confidence intervals are derived, it becomes easy to show that directional errors (that is, correct side decisions at each step) are simultaneously controlled with the familywise error rate (FWER). Adjabui, Howard and Luguterah (2017) proposed a simultaneous nonparametric upper bound procedure based on the Wilcoxon Mann-Whitney test in situations when normal assumptions are violated. Their paper incorporated the partitioning principle for confidence sets procedure proposed by Hsu and Berger (1999) for estimating MSD.…”
Section: Introductionmentioning
confidence: 99%
“…However, no multiplicity adjustment is necessary if the experimental groups (new treatments) can be ordered priori according to their treatment effect. Multiple treatments with stepwise procedure without multiplicity has been investigated by these authors but in different settings [8], [9] and [10] are shown to be more powerful than single step procedure. In their papers, they assumed that treatments have the same variances.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we simultaneously compare each of the treatments with the negative control. Statistical decision in this settings involves multiple comparison and stepwise procedures: that is, individual inferences are made in stepwise manner if the sequence of individual inferences is in a specific order, as used in Stefensson et al [2], Cao et al [3], Chen [4], and Adjabui et al [5]. Some simultaneous inferences remit multiplicity adjustments by invoking the partition principle proposed by Finner and Strassburger [6]: where the parameter space is partitioned into many disjoint subsets and only one of these nonempty disjoint subsets contains the true parameter of interest, so that the FWER will be properly controlled.…”
Section: Introductionmentioning
confidence: 99%